Vulvar Adenocarcinoma of Intestinal Type: A Case Report of an Uncommon Entity. (January 2022) - Moscoso, Olivier; Reques, Armando; Saco, Adela; Castellví, Josep; Gómez-Hidalgo, Natalia R.; Ramón y Cajal, Santiago; García, Ángel
Abstract : Vulvar cancer is rare and accounts for only 5% of all gynecologic cancers. Squamous cell carcinoma is the most common and makes up 90% of the cases. Vulvar adenocarcinoma usually arises in Bartholin and other vulvar glands. Primary vulvar intestinal-type adenocarcinoma is an extremely rare disease with an unclear prognosis and treatment. Its origin is still unknown, the most accepted theory suggests cloacal remnants as the source of origin. Only a few cases have been reported in the literature. We present a case of a 66-yr-old female who presented with vulvar pruritus and local discomfort, showing a 2 cm tumor located in the left labium minor in the region of vulvar fourchette. Wide vulvar excision and bilateral lymph nodes dissection were performed. Other concomitant lesions and distant extension of tumor were ruled out by positron emission tomography. Pathologic study revealed a colonic-type adenocarcinoma with typical villoglandular architecture with an irregular glandular structure composed of atypical columnar epithelium. The lesion had direct contact with epidermal surface and mainly was external without involving the dermis. Immunohistochemical analysis revealed positive staining for cytokeratin 20 and CDX2. p16 showed an abnormal diffuse and strong immunoexpression. The presence of a low-risk human papillomavirus was detected by polymerase chain reaction, therefore, the expression of p16 cannot be explained in this case by the presence of human papillomavirus. Additional studies are needed in additional cases to clarify the role of human papillomavirus in this kind of tumor.